PERSPECTIVES ON THE SCANDINAVIAN CULTURAL IMAGINARY FOREWORD - Roxana-Ema DREVE; Raluca-Daniela DUINEA; Raluca POP (Studia Universitatis Babeş-Bolyai. Philologia, 2023)
Issue 2/2023 of the Journal Studia Universitas Babeș-Bolyai. Philology, entitled Perspectives on the Scandinavian Cultural Imaginary, contains contributions from Romanian and foreign researchers who tackle a broad variety of subjects connected to Scandinavia. What brings these papers together, despite the heterogeneous topics and theoretical approaches, is the analysis of different cultural, literary or linguistic sets of images that articulate the concept of “imaginary” in the far North. Apart from the exploration of the “self” in relation to others, both reality, fiction, history and memory have been re-evaluated through the lens of the imaginary.